The potential of Myricitrin, a Flavonoid Compound in Eugenia polyantha from Indonesia, as an Antiviral Drug for SARS-Cov-2 through the Molecular Docking Analysis - Syamsul Falah; Laksmi Ambarsari; Rini Kurniasih; Sanro Tachibana; Dimas Andrianto (Jurnal Kimia Sains dan Aplikasi, 2023)
A Flavonoid glycoside compound, isolated and identified from E. polyantha as myricitrin, was analyzed as a ligand for its molecular binding activity against SARS-CoV-2 protein (receptor binding domain on Spike/RBD, main protease/nsp5, EndoRNAse, RNA-dependent-RNA-polymerase/RdRp), and its receptor, ACE2, and computationally assessed via molecular docking method. This study aims to determine the potential of myricitrin in E. polyantha from Indonesia as an antiviral drug for SARS-CoV-2 through molecular docking and molecular dynamic simulation analysis. The results showed that the myricitrin had the strongest binding affinity energy towards the three important SARS-CoV-2 proteins, namely endoRNAse, main protease (3CLpro), and RdRp with ∆G values of −9.60 kcal/mol, −8.40 kcal/mol, and −8.30 kcal/mol, respectively. These values are stronger than the comparator ligands of favipiravir (−5.60 kcal/mol), atazanavir (−7.20 kcal/mol), and remdesivir (−7.70 kcal/mol). This indicated that the compound has the potential as an inhibitor against 3CLpro, endoRNAse, and RdRp of SARS-CoV-2 proteins. This result was supported by the prediction made according to the Molprobity and PASS Online web servers, which showed that myricitrin has high bioactivity potential as an enzyme inhibitor (with a score of 0.38) and antiviral (with a score of 0.704).